The Social Accounting Matrix as a working instrument for defining economic policy. Application in Portugal with emphasis on the general government sector - Santos, Susana (2009)
The study of the Social Accounting Matrix, usually known as SAM, arises from the need to place sectors within the general context of the economy, as well as the need to find out more about the effects of macroeconomic policies at the sectoral level and sectoral policies at the macroeconomic level. Based on the principle that the study of a sector should be carried out under a general equilibrium approach, moving beyond the context of partial equilibrium, the SAM is one possibility for meeting such needs, in that it provides a complete account of the circular flow in the economy. After presenting the general characteristics of their framework, three SAMs (1997¬1999) will be constructed, with emphasis on the General Government sector. These will be created from the more recent data of the Portuguese System of National Accounts, the harmony between them both being demonstrated for the first year by identifying the identities and balances of the system's various internal accounts on the constructed matrix. The modelling of the constructed SAMs will begin with the deduction and decomposition of accounting multipliers, which will be used to study the impact of Economic Policy measures, namely Budget Policy, on the Portuguese economy. Tests will be performed to check the veracity of the SAMs, using both accounting and fixed-price multipliers. It will be concluded that the SAM is a working instrument providing a database that can be specially designed for specific economic analysis, as well as decision-making purposes.